The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.24974/amae.14.3.405
|View full text |Cite
|
Sign up to set email alerts
|

In a State of Becoming: How Institutions Communicate Asian American and Pacific Islander- and Latinx-Servingness Through Campus Artifacts

Abstract: This study examines the ways campus artifacts communicate Asian American and Pacific Islander (AAPI)- and Latinx-servingness at dually designated Asian American and Native American Pacific Islander-Serving Institutions (AANAPISIs) and Hispanic-Serving Institutions (HSIs). Using critical ethnographic methods, the researchers collected data at three AANAPISI- HSIs regionally concentrated in a western state. Findings from this study reveal that the campus environments of the three institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…While not within the community college context, there are several studies that revealed how imagery, visual representation, and physical artifacts impact students' belonging (Alcantar et al, 2022(Alcantar et al, , 2020 This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Visual Mediums' Impact On Lgbtqia+ Students' Identity Develo...mentioning
confidence: 99%
See 3 more Smart Citations
“…While not within the community college context, there are several studies that revealed how imagery, visual representation, and physical artifacts impact students' belonging (Alcantar et al, 2022(Alcantar et al, , 2020 This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Visual Mediums' Impact On Lgbtqia+ Students' Identity Develo...mentioning
confidence: 99%
“…They posit the importance of institutions to contend with what symbols communicate about who they value, who belongs, and what is communicated in terms of DEI commitments. These studies postulate that physical artifacts within higher education systems must (re)create physical and symbolic spaces to understand how such structures communicate belongingness (Alcantar et al, 2022(Alcantar et al, , 2020Yi et al, 2022).…”
Section: Visual Mediums' Impact On Lgbtqia+ Students' Identity Develo...mentioning
confidence: 99%
See 2 more Smart Citations
“…HSIs, community colleges, and higher education institutions in minority-majority states, such as those presented in this article, are not all alike and do not always use culturally responsive approaches to “serve” Latinx students (Garcia et al, 2019; Garcia & Okhidoi, 2015). Scholars have found significant variation in HSIs in the campus cultures, practices, and commitments to Latinx students and communities (Alcantar et al, 2020; Garcia et al, 2019; Núñez et al, 2016).…”
Section: Promoting the Civic Development Of Latinx College Studentsmentioning
confidence: 99%